2019
DOI: 10.1002/smll.201900236
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh‐Detectivity Photodetectors with Van der Waals Epitaxial CdTe Single‐Crystalline Films

Abstract: Van der Waals epitaxy (vdWE) is crucial for heteroepitaxy of covalence‐bonded semiconductors on 2D layered materials because it is not subject to strict substrate requirements and the epitaxial materials can be transferred onto various substrates. However, planar film growth in covalence‐bonded semiconductors remains a critical challenge of vdWE because of the extremely low surface energy of 2D materials. In this study, direct growth of wafer‐scale single‐crystalline cadmium telluride (CdTe) films is achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 35 publications
2
48
0
Order By: Relevance
“…Recently, Lian and his colleagues presented a wafer‐scale CdTe membrane on the mica substrate by a molecular beam epitaxy method. [ 65 ] This ultralarge film has significant potential application in future integrated devices. After characterizing the high crystal quality of this CdTe single‐crystalline membranes, authors reported a high‐performance photodetector with high responsivity (834 A W −1 ), high D * (2.4 × 10 14 Jones) and flexible properties on the basis of CdTe semiconductors.…”
Section: Photodetectors Based On Single 2d Materialsmentioning
confidence: 99%
“…Recently, Lian and his colleagues presented a wafer‐scale CdTe membrane on the mica substrate by a molecular beam epitaxy method. [ 65 ] This ultralarge film has significant potential application in future integrated devices. After characterizing the high crystal quality of this CdTe single‐crystalline membranes, authors reported a high‐performance photodetector with high responsivity (834 A W −1 ), high D * (2.4 × 10 14 Jones) and flexible properties on the basis of CdTe semiconductors.…”
Section: Photodetectors Based On Single 2d Materialsmentioning
confidence: 99%
“…In a semiconductor with low crystalline quality, there are more defects and grain boundaries, which is not conducive to the separation and transmission of photogenerated carriers. Therefore, improving the crystalline quality of semiconductors is one of the most effective ways to build high-performance self-powered UV detectors [ 78 , 79 , 80 , 81 , 82 ].…”
Section: Improving the Performance Of Self-powered Uv Photodetectors ...mentioning
confidence: 99%
“…Wang et al. [ 269 ] introduced a vdW epitaxy 2D CdTe photodetector by the PCE, as shown in Figure a. They found that the CdTe photodetector demonstrates ultrasensitive photoresponse of R = 834 A W −1 , high detectivity of D* = 2.4 × 10 14 Jones (Figure 12b), and fast response speed of τ rising /τ decay = 2.6/3.4 ms (Figure 12c).…”
Section: Applicationsmentioning
confidence: 99%
“…Reproduced with permission. [ 269 ] Copyright 2019, Wiley‐VCH. d) Schematic diagram of the PGE MoTe 2 photodetector; e) Schematic of the PGE, where E c , E f , E v , V d are the conduction band, Fermi level, valence band, and bias voltage, respectively.…”
Section: Applicationsmentioning
confidence: 99%